2011
DOI: 10.2478/v10156-010-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Planar, spherical and ellipsoidal approximations of Poisson's integral in near zone

Abstract: Abstract:Planar, spherical, and ellipsoidal approximations of Poisson's integral for downward continuation (DWC) of gravity anomalies are discussed in this study. The planar approximation of Poisson integral is assessed versus the spherical and ellipsoidal approximations by examining the outcomes of DWC and finally the geoidal heights. We present the analytical solution of Poisson's kernel in the point-mean discretization model that speed up computation time 500 times faster than spherical Poisson kernel while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The numerical error can be mitigated through regularization (e.g., Novák et al, 2001;Kingdon and Vaníček, 2011). Even without regularization, the error in geoid determination resulting from the ill conditioning of the downward continuation of gravity values only reaches a few centimeters in regions with elevations over 3 km (e.g., Huang, 2002;Goli, 2011), and less at lower elevations.…”
Section: The Determination Of the Geoidmentioning
confidence: 99%
“…The numerical error can be mitigated through regularization (e.g., Novák et al, 2001;Kingdon and Vaníček, 2011). Even without regularization, the error in geoid determination resulting from the ill conditioning of the downward continuation of gravity values only reaches a few centimeters in regions with elevations over 3 km (e.g., Huang, 2002;Goli, 2011), and less at lower elevations.…”
Section: The Determination Of the Geoidmentioning
confidence: 99%
“…However, as suggested by Novak et al (2001) and demonstrated by Kingdon and Vanicek (2011), the ill-conditioning can be mitigated through regularization, and even without regularization Huang (2002) claimed that the geoid error only reaches a few centimetres in regions with elevations over 3 kilometres. Goli and Najafi (2011) showed that planar approximation of the Poisson equation can considerably speed up the laborious computational process at the prize of about 1 cm additional uncertainty in the geoid height.…”
Section: The Dwc Effect In the Rcr Techniquementioning
confidence: 99%